Method for measuring potential difference of diffusion layer in solid-liquid interface double electric layer
By building a three-electrode system on the surface of steel and titanium alloys, measuring the potential difference of the diffusion layer is solved, and the limitations and safety risks of traditional methods on these materials are achieved, and the measurement of higher accuracy and stability is achieved. It is suitable for complex electrolyte systems and avoids the use of mercury toxicity problem.
Patent Information
- Application Number
- CN202411428523.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to accurately measure the potential difference of the diffusion layer on the surface of metal materials such as steel and titanium alloys, and the traditional mercury drop electrode method has limitations and safety risks, making it difficult to apply to a wider range of electrochemical fields.
Using a method of measuring the potential difference of the diffusion layer in the double layer of the solid-liquid interface, through sample preparation, three-electrode system construction and data measurement processing, including encapsulating the sample with epoxy resin, building a three-electrode system and electrochemically through Gamry Interface 1000 Test, calculate the potential difference of the diffusion layer.
The potential difference of the diffusion layer is successfully measured on the surface of steel and titanium alloys, which improves the measurement accuracy and stability. It is suitable for high-concentration electrolyte systems, avoids the toxicity of mercury, and complies with the principle of green chemistry.
Smart Images

Figure CN119269603A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of corrosion protection, and in particular relates to a method for measuring the potential difference of a diffusion layer in a double electric layer at a solid-liquid interface. Background Art
[0002] In existing measurement technology, especially in the field of metal corrosion protection, the diffusion layer potential difference is usually not considered for the sake of simplicity. Only the potential difference from the electrode surface to the solution is of interest The ion concentration distribution near the electrode surface and its influence are often ignored, resulting in an incomplete description of the interfacial potential. Considering the diffusion layer potential difference can more accurately describe the potential gradient between the electrode surface and the electrolyte solution, especially under low ionic strength or high charge density conditions. The diffusion layer potential difference is crucial for understanding the local potential and reaction mechanism of the electrode surface. It helps to reveal the charge distribution and ion concentration distribution near the electrode surface, and better explain the occurrence of interfacial phenomena in electrochemical reactions and their effects on electrode reactions. Especially when there is obvious ion diffusion in the double electrical layer, the mass transfer process significantly affects the reaction rate, such as reactions with large changes in ion concentration near the electrode surface. By accurately describing the diffusion layer, the contribution of diffusion control to the electrochemical reaction rate can be better understood.
[0003] In addition, the diffusion layer potential difference affects the double layer capacitance and electrochemical impedance at the electrode / electrolyte interface. Considering the diffusion layer potential difference helps to improve the accuracy of differential capacitance and electrochemical impedance measurements, thereby helping to analyze the charge distribution and interface reaction characteristics on the electrode surface. For electrochemical sensors, especially those based on ion selection, changes in the diffusion layer potential difference can provide a more sensitive response to ion concentration. Therefore, considering the influence of the diffusion layer potential difference can improve the accuracy of electrochemical sensors. In electrochemical energy storage devices (such as supercapacitors, batteries, etc.), the potential difference of the double layer, especially the diffusion layer, affects the performance and reaction efficiency of the electrode material. If the diffusion layer potential difference is ignored, it may lead to limitations in the design of electrode materials. For example, in supercapacitors, the double layer capacitance is the main energy storage mechanism, and the diffusion layer potential difference directly affects the energy storage capacity. By considering the diffusion layer potential difference, electrode materials can be designed more accurately and the performance of energy storage devices, such as capacitance and energy density, can be optimized, and the electrode stability and life can be improved. In terms of corrosion assessment, the corrosion reaction occurs at the electrode / solution interface, and the change in the diffusion layer potential difference reflects the kinetics of the redox reaction on the electrode surface and the change in ion concentration. If the diffusion layer is not considered, the rate of the corrosion process may be underestimated. When localized corrosion or pitting occurs, the solid-liquid interface mass transfer process is obvious, and the potential difference of the diffusion layer can significantly affect the corrosion rate. Considering the potential difference of the diffusion layer helps to predict the corrosion rate more accurately.
[0004] At present, the research and technical development of the measurement method of the diffusion layer potential difference in the literature and the market are relatively limited. The traditional measurement method mainly relies on the mercury drop electrode. Due to its liquid surface properties and easy-to-control experimental conditions, the mercury drop electrode was widely used in the early days to study the double layer characteristics of the electrode / electrolyte interface, especially in electrolyte solutions that do not adsorb ions, such as sodium fluoride (NaF). These experiments usually combine techniques such as AC impedance and potential scanning to record the electrochemical behavior related to the diffusion layer by changing the potential of the electrode, thereby inferring the potential difference between the electrode surface and the diffusion layer. However, this measurement method has significant limitations: due to the properties of the mercury electrode, its measurement object can only be limited to the diffusion layer potential difference on the surface of the mercury drop, and it is difficult to apply it on the surface of other metal materials (such as steel and titanium alloys) and other electrolyte systems. This greatly limits its application in a wider range of electrochemical fields. In addition, the chemical and physical properties of mercury, especially its toxicity, make this method have certain hidden dangers in terms of environment and health, and the treatment and waste management of mercury are also important issues. Although the mercury drop electrode has unique advantages in the basic research of the double electric layer on the electrode surface, its defects in applicability and safety have led scientists to seek new methods to expand the scope of application of diffusion layer potential difference measurement. Summary of the invention
[0005] To solve the above problems, the present invention provides a method for measuring the potential difference of the diffusion layer in the double electric layer at the solid-liquid interface. The method can successfully measure the potential difference of the diffusion layer on the surface of metal materials such as steel and titanium alloy.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] The present invention provides a method for measuring the potential difference of the diffusion layer in the double electric layer of the solid-liquid interface. The following formula is used for calculation:
[0008]
[0009] Among them, α is the charge transfer coefficient, α * is the charge transfer coefficient under non-ideal conditions, n is the number of charges gained or lost in the redox reaction, is the electrode potential, The electrode is at equilibrium potential, z O is the relative charge of the oxidation state.
[0010] Furthermore, it also includes building a test system, and the building method of the test system is: sample preparation; building a three-electrode system; data measurement and processing.
[0011] Furthermore, the sample preparation includes: cutting blocks of preset sizes, grinding, polishing, cleaning and packaging the surfaces of the blocks.
[0012] Furthermore, the grinding process is: use sandpaper of different particle sizes to gradually grind the surface of the pure iron sample, and use sandpaper with a minimum mesh of 1200 for final grinding until the surface is smooth and has no obvious scratches; after each step of grinding, rinse the sample with deionized water and wipe the surface with ethanol.
[0013] Furthermore, the polishing process is: further polishing the sample using a polishing paste with a specification of 1 μm or less until the sample surface has a mirror effect.
[0014] Furthermore, the cleaning is: placing the sample in an ultrasonic cleaner, cleaning with deionized water and ethanol for at least 5 minutes each, and finally blowing the sample surface dry with dry nitrogen.
[0015] Furthermore, the encapsulation is as follows: the sides and back of the sample are completely encapsulated with epoxy resin, leaving only the working surface exposed; after the encapsulation is completed, ensure that the epoxy resin is in close contact with the sample without bubbles or gaps.
[0016] Furthermore, the area of the working surface is 10 mm×10 mm.
[0017] Furthermore, the method for constructing the three-electrode system includes: working electrode installation: installing the packaged pure iron sample at the working electrode position of the three-electrode system, and connecting it to Gamry Interface 1000 through a wire; counter electrode installation: placing a 10 mm × 30 mm platinum sheet as a counter electrode in an electrolytic cell and connecting it to an electrochemical workstation through a wire; reference electrode installation: inserting a saturated calomel electrode or AgCl electrode into the electrolyte, and connecting the reference electrode to Gamry Interface 1000 through a wire; electrolyte preparation: preparing an electrolytic solution, stirring it thoroughly until the solution is uniform, and pouring the solution into the electrolytic cell to ensure that the electrodes of the three-electrode system are all immersed in the solution.
[0018] Furthermore, during the data measurement and processing, when the potential variation amplitude is less than 0.2 mV / min, it is considered that the OCP has reached a stable state, and the final open circuit potential value is recorded.
[0019] The beneficial effects brought by the technical solution provided by the embodiment of the present invention include:
[0020] (1) The present invention can successfully measure the diffusion layer potential difference on the surface of metal materials such as steel and titanium alloys, which is difficult to achieve in the traditional mercury drop electrode system. Steel and titanium alloys have attracted much attention due to their wide range of industrial applications (such as structural materials in the aerospace, shipbuilding and automotive industries), and their surface electrochemical behavior is crucial to the corrosion resistance and long-term stability of the materials. The ability to measure the diffusion layer potential difference on the surface of these materials provides an important experimental basis for understanding the corrosion mechanism of metal surfaces and optimizing anti-corrosion measures. This technological breakthrough not only expands the diversity of experimental materials, but also makes it possible to measure in more complex electrolyte systems, especially in high-concentration electrolytes such as sodium hydroxide (NaOH), sodium chloride (NaCl) and other solutions. The measurement of the diffusion layer potential difference can be achieved, which provides more possibilities for the study and control of electrochemical processes in practical industrial applications.
[0021] (2) These new measurement methods are not only limited to the expansion of materials and electrolyte systems, but also greatly improve the accuracy and stability of measurements. Compared with the traditional mercury drop electrode, these new technologies can better cope with experimental conditions at high potential and high current density, ensuring the accuracy and reproducibility of the measurement results. At the same time, the measurement method provided by the present invention can avoid the toxicity problem of mercury and adopts more environmentally friendly and safe experimental equipment and electrode materials, which not only helps to improve the safety of laboratory operations, but also complies with the green chemistry principles that are increasingly valued in modern chemical experiments.
[0022] (3) In terms of measurement accuracy, the new technology makes the measurement of diffusion layer potential difference more accurate and rapid by improving electrode design, optimizing experimental parameters and data acquisition methods. In particular, it can better capture transient potential changes in dynamic electrochemical processes. This improvement is of great significance for studying electrochemical reaction kinetics, interface phenomena and diffusion layer behavior in complex multiphase systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0024] Figure 1 A schematic diagram of the double electric layer structure and potential distribution of the GCS provided in an embodiment of the present invention;
[0025] Figure 2 Potentiodynamic polarization test at 25°C and 50°C provided in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] like Figure 1 As shown in the model, the embodiment of the present invention provides a method for measuring the potential difference of the diffusion layer in the double electric layer at the solid-liquid interface. The following formula is used for calculation:
[0028]
[0029] Among them, α is the charge transfer coefficient, α * is the charge transfer coefficient under non-ideal conditions, n is the number of charges gained or lost in the redox reaction, is the electrode potential, The electrode is at equilibrium potential, z O is the relative charge of the oxidation state.
[0030] The present invention can successfully measure the diffusion layer potential difference on the surface of metal materials such as steel and titanium alloy, which is difficult to achieve in the traditional mercury drop electrode system. Steel and titanium alloys have attracted much attention due to their wide industrial applications (such as structural materials in the aerospace, shipbuilding and automotive industries), and their surface electrochemical behavior is crucial to the corrosion resistance and long-term stability of the materials. The ability to measure the diffusion layer potential difference on the surface of these materials provides an important experimental basis for understanding the corrosion mechanism of metal surfaces and optimizing anti-corrosion measures. This technological breakthrough not only expands the diversity of experimental materials, but also makes it possible to measure in more complex electrolyte systems, especially in solutions of high-concentration electrolytes such as sodium hydroxide (NaOH) and sodium chloride (NaCl), the measurement of the diffusion layer potential difference can be achieved, which provides more possibilities for the study and control of electrochemical processes in practical industrial applications. In addition, these new measurement methods are not only limited to the expansion of materials and electrolyte systems, but also greatly improve the accuracy and stability of the measurement. Compared with traditional mercury drop electrodes, these new technologies can better cope with experimental conditions at high potentials and high current densities, ensuring the accuracy and reproducibility of measurement results. At the same time, the measurement method provided by the present invention can avoid the toxicity problem of mercury and adopts more environmentally friendly and safe experimental devices and electrode materials, which not only helps to improve the safety of laboratory operations, but also complies with the green chemistry principle that is increasingly valued in modern chemical experiments. In terms of measurement accuracy, the new technology makes the measurement of the diffusion layer potential difference more accurate and rapid by improving the electrode design, optimizing the experimental parameters and data acquisition methods, especially in the dynamic electrochemical process, it can better capture the transient potential changes. This improvement is of great significance for studying the electrochemical reaction kinetics, interface phenomena and the diffusion layer behavior in complex multiphase systems.
[0031] Specifically, in the ideal reaction, α is taken as 0.5; is the electrode potential, The electrode is at equilibrium potential, η is the overpotential, and the obtained data are processed using the supporting software of the electrochemical workstation to draw the potential-current density curve. The overpotential η can be obtained by subtracting OCP from the actual polarization curve potential; the charge transfer coefficient α under non-ideal conditions can be obtained by fitting the region of equilibrium potential ±50mV using the following formula: * .
[0032]
[0033] Among them, β * is the charge transfer coefficient under non-ideal conditions, β * =1-α * , I0 is the exchange current density, F is the Faraday constant, R is the gas constant, T is the absolute temperature, I F is the electrochemical reaction current density.
[0034] Specifically, it also includes building a test system, and the building method of the test system is:
[0035] S1 Sample preparation.
[0036] The sample preparation includes: cutting blocks of preset sizes, grinding, polishing, cleaning and packaging the surfaces of the blocks.
[0037] The grinding process is as follows: using sandpapers of different grits to gradually grind the surface of the pure iron sample, and using sandpaper with a minimum mesh of 1200 for final grinding until the surface is smooth and has no obvious scratches; after each step of grinding, rinsing the sample with deionized water and wiping the surface with ethanol.
[0038] The polishing process is: further polishing the sample using a polishing paste with a specification of 1 μm or less until the sample surface has a mirror effect.
[0039] The cleaning is as follows: placing the sample in an ultrasonic cleaner, cleaning with deionized water and ethanol for at least 5 minutes each, and finally blowing the sample surface dry with dry nitrogen.
[0040] The packaging is as follows: the side and back of the sample are completely packaged with epoxy resin, leaving only the working surface exposed; after the packaging is completed, ensure that the epoxy resin is in close contact with the sample without bubbles or gaps.
[0041] Specifically, the area of the working surface is 10 mm×10 mm.
[0042] Construction of the S2 three-electrode system.
[0043] The method for constructing the three-electrode system comprises:
[0044] Working electrode installation: Install the packaged pure iron sample at the working electrode position of the three-electrode system and connect it to the Gamry Interface 1000 via a wire.
[0045] Counter electrode installation: A 10 mm × 30 mm platinum sheet was used as a counter electrode, placed in the electrolytic cell and connected to the electrochemical workstation via a wire.
[0046] Reference electrode installation: Insert the saturated calomel electrode or AgCl electrode into the electrolyte and connect the reference electrode to the Gamry Interface 1000 via a wire.
[0047] Preparation of electrolyte: prepare the electrolyte solution, stir it thoroughly until the solution is uniform, and pour the solution into the electrolytic cell to ensure that the electrodes of the three-electrode system are immersed in the solution. The electrolyte can be NaCl, NaOH, dilute sulfuric acid, dilute hydrochloric acid, KOH, KCl, etc., and the molar concentration shall not exceed 0.8 mol / L.
[0048] S3 data measurement and processing.
[0049] The electrolytic cell was placed in a preset temperature system, and then the open circuit potential (OCP) and potentiodynamic polarization curve tests were measured.
[0050] Plot the potential-current density curve, subtract OCP from the actual polarization curve potential to get the overpotential η, and fit the region of the equilibrium potential ±50mV using equation (2) to get the charge transfer coefficient α under non-ideal conditions. * According to formula (1), the diffusion layer potential difference under different temperatures and overpotentials can be obtained
[0051] Example 1
[0052] 1. Experimental Materials and Equipment
[0053] 1.1 Materials
[0054] Pure iron sample: size is 10mm×10mm×5mm, exposed surface area is 10mm×10mm.
[0055] Epoxy resin: used to encapsulate the working electrode to prevent the surface other than the exposed part of the electrode from contacting the electrolyte.
[0056] 0.6mol / L NaCl solution: used as electrolyte to simulate the corrosive environment.
[0057] Platinum sheet (counter electrode): size is 10mm×30mm, with good conductivity and chemical inertness.
[0058] Saturated calomel electrode (reference electrode): used to provide a stable reference potential.
[0059] 1.2 Experimental equipment
[0060] Gamry Interface 1000 Potentiostat: For controlling and recording electrochemical tests.
[0061] Constant temperature water bath: used to maintain the experimental temperature at 25℃.
[0062] Three-electrode system container: includes the installation positions of the working electrode, counter electrode and reference electrode.
[0063] Sandpaper and polishing paste: used for surface treatment of pure iron samples.
[0064] 2. Sample Preparation
[0065] 2.1 Cutting and cleaning of pure iron samples
[0066] Cutting: Use a metal cutting machine to cut the pure iron sample into 10mm×10mm×5mm specifications, ensuring that the exposed area of each sample is 100mm 2 .
[0067] Surface grinding: Use sandpaper of different grits (such as 320, 600, 800, 1000 and 1200 mesh) to gradually grind the surface of the pure iron sample until its surface is smooth and without obvious scratches. To ensure the cleanness of the sample surface, rinse the sample with deionized water and wipe the surface with ethanol after each step of grinding.
[0068] Polishing: The sample was further polished using a 1 μm polishing paste until the sample surface had a mirror effect to reduce the impact of surface defects on the electrochemical test.
[0069] Ultrasonic cleaning: Place the sample in an ultrasonic cleaner and clean it with deionized water and ethanol for 5 minutes each. Finally, blow dry the sample surface with dry nitrogen.
[0070] 2.2 Epoxy resin encapsulation
[0071] Encapsulation: Use epoxy to completely encapsulate the sides and back of the sample, leaving only a 10mm x 10mm working surface area exposed. Ensure that the epoxy is fully cured to prevent the electrolyte from contacting the encapsulated part.
[0072] Check the packaging quality: After the packaging is completed, ensure that the epoxy resin is in close contact with the sample without bubbles or gaps that may affect the experimental results.
[0073] 3. Assembly of the Three-Electrode System
[0074] Working electrode installation: Install the packaged pure iron sample at the working electrode position of the three-electrode system and connect it to the Gamry Interface 1000 via a wire.
[0075] Counter electrode installation: Place a 10 mm × 30 mm platinum sheet as the counter electrode in the electrolytic cell, ensure that it is in full contact with the electrolyte, and connect it to the electrochemical workstation via a wire.
[0076] Reference electrode installation: Insert the saturated calomel electrode into the electrolyte, making sure it is close to the working electrode to reduce the potential error caused by ohmic resistance. The reference electrode is connected to the Gamry Interface 1000 via a wire.
[0077] Preparation of electrolyte: Prepare 0.6 mol / L NaCl solution and stir thoroughly until the solution is uniform. Pour the solution into the electrolytic cell, making sure that all electrodes of the three-electrode system are immersed in the solution.
[0078] 4. Experimental Procedure
[0079] 4.1 Constant temperature water bath setting
[0080] Water bath preparation: Place the electrolytic cell in a constant temperature water bath and adjust the temperature control system to keep the solution temperature at 25°C. During the experiment, the temperature of the electrolyte is precisely controlled by the constant temperature water bath system to ensure stable temperature during the experiment.
[0081] Temperature monitoring: Use a thermometer to monitor the temperature of the electrolyte in real time to ensure that the temperature error does not exceed ±0.5℃.
[0082] 4.2 Determination of open circuit potential (OCP)
[0083] Start the electrochemical workstation: Start the Gamry Interface 1000 electrochemical workstation and select the three-electrode system configuration.
[0084] Determine the open circuit potential: Record the open circuit potential (OCP) of the working electrode without applying an external current. Observe the change in potential and wait for the OCP to reach a stable state, which usually takes 10 to 20 minutes.
[0085] Stability verification: When the potential change amplitude is less than 0.2mV / min, the OCP is considered to have reached a stable state, and the final open circuit potential value is recorded.
[0086] 4.3 Potentiodynamic polarization curve test
[0087] Polarization parameter setting: Set the test parameters on the electrochemical workstation, including the starting potential, the ending potential and the scan rate. The scan rate should not be too fast, and the general scan rate is set to 0.33mV / s.
[0088] Polarization test starts: After the OCP stabilizes, the sample is subjected to potentiodynamic polarization test at a rate of 0.33 mV / s, and the potential-current density data are recorded.
[0089] Data collection and storage: Real-time monitoring of the change of current density with potential, and automatic data recording through the electrochemical workstation. After the test is completed, the data is exported and saved for subsequent analysis and processing.
[0090] 6. Data Analysis
[0091] Data processing: The obtained data were processed using the supporting software of the electrochemical workstation to draw the potential-current density curve. The overpotential η was obtained by subtracting the OCP from the actual polarization curve potential. The charge transfer coefficient α under non-ideal conditions was obtained by fitting the region of ±50 mV of the equilibrium potential using formula (2). * , the measurement and data processing results are as follows Figure 2 As shown. For the solution used, such as the NaCl solution here, n = 1, ZO = 1, and α = β = 0.5 in an ideal state, according to formula (1), it can be obtained that at 25°C, At 50℃, When η=0.05V, what is the The values are shown in Table 1.
[0092] Table 1 Diffusion layer potential difference at different temperatures and overpotentials
[0093]
[0094] 7. Experimental Notes
[0095] Influence of sample surface condition: Oxides and contaminants on the sample surface will have a significant impact on the electrochemical test results. Therefore, special attention should be paid when treating the sample surface to ensure that the sample surface is flat and clean.
[0096] Control of solution temperature: The temperature changes of the solution should be closely monitored during the experiment to avoid the impact of temperature fluctuations on the test results.
[0097] Installation and connection of electrodes: Ensure that the electrodes of the three-electrode system are firmly connected and that the immersion depth of each electrode in the electrolyte is appropriate to avoid data errors caused by poor contact or unstable connection.
[0098] Post-test processing: After the experiment, clean and dry the electrodes immediately to avoid further corrosion of the sample or changes in the surface passivation film.
[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for measuring the potential difference of the diffusion layer in the double electric layer at the solid-liquid interface, characterized in that: The diffusion layer potential difference The following formula is used for calculation: Among them, α is the charge transfer coefficient, α * is the charge transfer coefficient under non-ideal conditions, n is the number of charges gained or lost in the redox reaction, is the electrode potential, The electrode is at equilibrium potential, z O is the relative charge of the oxidation state.
2. The method according to claim 1, characterized in that: It also includes building a test system, and the building method of the test system is: Sample preparation; Construction of three-electrode system; Data measurement and processing.
3. The method according to claim 2, characterized in that The sample preparation includes: cutting blocks of preset sizes, grinding, polishing, cleaning and packaging the surfaces of the blocks.
4. The method according to claim 3, characterized in that The grinding process is as follows: using sandpapers of different grits to gradually grind the surface of the pure iron sample, and using sandpaper with a minimum mesh of 1200 for final grinding until the surface is smooth and has no obvious scratches; after each step of grinding, rinsing the sample with deionized water and wiping the surface with ethanol.
5. The method according to claim 3, characterized in that: The polishing process is: further polishing the sample using a polishing paste with a specification of 1 μm or less until the sample surface has a mirror effect.
6. The method according to claim 3, characterized in that The cleaning is as follows: placing the sample in an ultrasonic cleaner, cleaning with deionized water and ethanol for at least 5 minutes each, and finally blowing the sample surface dry with dry nitrogen.
7. The method according to claim 3, characterized in that The packaging is as follows: the side and back of the sample are completely packaged with epoxy resin, leaving only the working surface exposed; after the packaging is completed, ensure that the epoxy resin is in close contact with the sample without bubbles or gaps.
8. The method according to claim 7, characterized in that The area of the working surface is 10 mm×10 mm.
9. The method according to claim 2, characterized in that: The method for constructing the three-electrode system comprises: Working electrode installation: Install the packaged pure iron sample at the working electrode position of the three-electrode system and connect it to the Gamry Interface 1000 via a wire. Counter electrode installation: A 10 mm × 30 mm platinum sheet was used as the counter electrode, placed in the electrolytic cell and connected to the electrochemical workstation via a wire; Reference electrode installation: Insert the saturated calomel electrode or AgCl electrode into the electrolyte, and connect the reference electrode to the Gamry Interface 1000 via a wire. Electrolyte preparation: prepare the electrolytic solution, stir it thoroughly until the solution is uniform, and pour the solution into the electrolytic cell to ensure that all electrodes of the three-electrode system are immersed in the solution.
10. The method according to claim 2, characterized in that During the data measurement and processing, When the potential change amplitude was less than 0.2 mV / min, the OCP was considered to have reached a stable state, and the final open circuit potential value was recorded.